“Aula prática de Brasil” : ditadura, estudantes universitários e imaginário nacionalista no Projeto Rondon (1967-1985) - Gabriel Amato Bruno de Lima (2015)
The theme of this dissertation is the university extension program Project Rondon from its creation by the military dictatorship, in 1967, to the end of general João Baptista Figueiredo government, in 1985. It is argued that the agents who took part on its operations (undergraduate students, professors, militaries, technicians) have constituted their practices along the program through a nationalist imaginary. The country’s interior was understood, in this sense, at the same time as a source of Brazilianness and as a space “empty” of nationality that should be “conquered” by the students. This imaginary included an anti-communist aspect to several actors from the regime, considering that, especially from 1967 to 1979, they hoped that the “practical lesson of Brazil” provided by the Rondon would alienate the students of political manifestations against the military regime, all labelled “communists”. From the point of view of the relations between the military dictatorship and the undergraduate students, the dissertation questions both the social memory constructed since 1979, which defends the thesis of the student as a dictatorship “natural” oppositionist, and part of the contemporary historiography which understands some social groups support to the authoritarianism as a “consensus” around the military regime. It defends, on the contrary, the existence of a social dynamic of the political regime established in 1964 which included a range of behaviours adopted by the students thorough time, such as adhesion, apathy, resistance and accommodation.